Front Cover: Integrated Photo‐Responsive Batteries for Solar Energy Harnessing: Recent Advances, Challenges, and Opportunities (ChemPlusChem 4/2020). Issue 4 (1st April 2020) - Fang, Zhengsong; Hu, Xuanhe; Yu, Dingshan
Abstract : The Front Cover shows an integrated photo‐responsive battery with the simplest two‐electrode configuration powering a vehicle under light illumination. The Taiji diagram shows the working principle of this device, which combines photoexcited electrons (e − ) and/or holes (h + ) with various redox species of the batteries during charging and/or discharging processes to realize the harnessing of solar energy. More details can be found in the Minireview by D. Yu et al. (DOI: 10.1002/cplu.201900608 ).